Russian Cinema. - Gillespie, David (Taylor and Francis, 2014)
Russian Cinema provides a lively and informative exploration of the film genres that developed during Russia's tumultuous history, with discussion of the work of Eisenstein, Pudovkin, Mikhalkov, Paradzhanov, Sokurov and others. The background section assesses the contribution of visual art and music, especially the work of the composers Shostakovich and Prokofev, to Russian cinema. Subsequent chapters explore a variety of topics: The literary space - the cinematic rendering of the literary text, from 'Sovietized' versions to bolder and more innovative interpretations, as well as adaptations of foreign classics The Russian film comedy looks at this perennially popular genre over the decades, from the 'domestication' of laughter under Stalin to the emergence of satire The historical film - how history has been used in film to affirm prevailing ideological norms, from October to Taurus Women and Russian film discusses some of the female stars of the Soviet screen (Liubov Orlova, Vera Alentova, Liudmila Gurchenko), as well as films made by male and female directors, such as Askoldov and Kira Muratova Film and ideology shows why ideology was an essential component of Soviet films such as The Maxim Trilogy, and how it was later definitively rejected The Russian war film looks at Civil War and Second World War films, and the post-Soviet treatment of recent conflicts in Afghanistan and Chechnya Private life and public morality explores the evolution of melodramas about youth angst, town and village life, personal relationships, and the emergence of the dominant sub-genre of the 1990s, the gangster thriller Autobiography, memory and identity offers a close reading of the work of Andrei Tarkovskii, Russia's greatest post-war director, whose films, including Andrei Rublev and Mirror, place him among the foremost European auteur film-makers Russian Cinema.